Peranan Keagenan dalam Perpanjangan Sertifikat Keselamatan Konstruksi Kapal Barang pada KSOP Merak Banten oleh PT. Vinci Samudera Agencies Cabang Merak Banten - Fransiskus Xaverius Pasaribu; Suratni Ginting; Muhammad Sahid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study examines the role of agents in the renewal process of cargo ship construction safety certificates at the Merak Banten Harbormaster and Port Authority Office (KSOP), using a case study of PT. Vinici Samudera Agencies, Merak Branch. The study aimed to determine the role of agency companies in assisting shipowners in fulfilling certification obligations and to examine certificate renewal procedures in accordance with legal provisions and shipping safety standards. The research methods employed included a field approach through direct observation, interviews, and a literature review of relevant literature, regulations, and official documents. Based on the research findings, PT. Vinici Samudera Agencies plays a significant role in processing shipping administrative documents, coordinating with the KSOP, ensuring compliance with applicable legal provisions, and providing technical guidance to ensure ships remain seaworthy. The agency's role has been proven to increase time efficiency, reduce the risk of delays, and provide legal certainty in the certificate renewal process. Therefore, the presence of ship agents is a strategic factor in supporting the smooth operation of cargo ships at the Port of Merak.